Chinese spirit mediumship: An exploratory study in Kuala Lumpur / Yong Lai Peng - Yong, Lai Peng (1985)

(untitled)
Chinese spirit mediumship is an intricate part of the Chinese religious system. A Chinese religions would at one time other had something to do with spirit mediumship. Thus, a study in this aspect may help enhance better understanding in the structure and organization of the Chinese religion. This graduation exercise seeks to explore the practices of Chinese spirit mediums focusing on branches i.e. temple mediums and soulraisers. Chapter II dealt with two concepts i.e. Shen and Gui, explaining the Chinese basic beliefs regarding divinity, life and death (Heaven, Earth and Underworld). Chapter III and IV are mainly descriptions of the practices of two temple mediums (known as Dangkis) and two soulraisers. It includes discussion of their functions, organizations, the trance phenomenon and other details such as the mediums personal background and clientele. In chapter V, a brief comparison between the two groups of mediums is made. The nature of Chinese spirit mediumship is upon bringing to light its few distinct characteristics. In conclusion, we ponder over the popularity or decline of the Chinese spirit mediumship in local environment.